Dépenses et utilisation de soins de santé: Une revue de littérature théorique et empirique - Jouilil Youness; Lechheb Houda; Ouakil Hicham (European Scientific Journal, ESJ, 2018)
This research paper will review the literature on both important theoretical and empirical studies in health microeconomics. For this purpose, the first part defines the health insurance scheme and its main objectives. The second part presents the theoretical framework of the health demand, in particular the effect of health insurance on the consumption of health care. Part III presents examples of previous empirical studies that have examined the effect of coverage by a health insurance scheme. The last paragraph presents the role of the other dimensions and their effects on the individual demand for health care. More specifically, this paper aims, among other things, to answer these questions. Does health insurance improve the state of health? How does it affect health expenditure? What are the problems of setting up comprehensive medical coverage? What is the case for other socioeconomic and sociodemographic and socio-cultural variables? It has been found from the analysis that there is a strong relationship between insurance and access to care. This observation has been confirmed through a synthesis of most of the work dealing with this issue.